Penerapan ISO 9001:2015 dalam Peningkatan Sasaran Mutu SMART di PT STK - Eko Widodo Gustany; Sinta Restuasih; Anggi Manullang; Zulhamidi Zulhamidi (TECHNO-SOCIO EKONOMIKA, 2025)
In the face of increasingly intense business competition, the implementation of an effective Quality Management System (QMS) has become a key factor in enhancing a company’s competitiveness. This study aims to analyze the implementation of the ISO 9001:2015 Quality Management System at PT. STK, focusing on the development of quality objectives based on the SMART principles (Specific, Measurable, Achievable, Relevant, and Time-bound) and the quantitative evaluation of their achievement. The research employed a descriptive quantitative method through document analysis, interviews, and direct observation. The data sources included the 2024 external ISO 9001:2015 audit results, documented quality objectives, and performance evaluation records. The findings revealed weaknesses in the formulation of quality objectives, particularly in terms of measurability and time-bound criteria, which reduced their effectiveness in supporting strategic decision-making. Prior to improvement, most quality objectives did not meet the measurable and time-bound aspects of SMART. After reformulation based on SMART principles and the implementation of quantitative performance evaluation, all divisional quality objectives fulfilled the SMART criteria. The improvement implemented through the PDCA (Plan-Do-Check-Act) approach led to significant enhancements in quality performance, as evidenced by a reduction in the product reject rate from 1.2% to 0.6% and an increase in the internal audit score from 78 (fair) to 90 (good). This study concludes that integrating SMART principles with quantitative evaluation and the PDCA cycle effectively improves QMS performance and product quality consistency. It is recommended that the company maintain periodic evaluations and strengthen cross-divisional involvement in the formulation and monitoring of quality objectives to ensure continuous improvement.